2003
DOI: 10.1067/mtc.2003.324
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump coronary artery bypass grafting provides complete revascularization with reduced myocardial injury, transfusion requirements, and length of stay: A prospective randomized comparison of two hundred unselected patients undergoing off-pump versus conventional coronary artery bypass grafting

Abstract: When compared with conventional coronary artery bypass grafting with cardiopulmonary bypass, off-pump coronary artery bypass grafting achieved similar completeness of revascularization, similar in-hospital and 30-day outcomes, shorter length of stay, reduced transfusion requirement, and less myocardial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
357
5
29

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(419 citation statements)
references
References 23 publications
(31 reference statements)
24
357
5
29
Order By: Relevance
“…A standardized OPCAB approach in high-risk patients does not come at a price of less complete revascularization. This is an important aspect that has been highlighted to be a crucial predictor for the long-term outcome [7,8], but has also been reported to be a major argument against OPCAB [11,24,25]. Our findings are supported by Puskas et al [8] who demonstrated feasibility of complete revascularization using OPCAB.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A standardized OPCAB approach in high-risk patients does not come at a price of less complete revascularization. This is an important aspect that has been highlighted to be a crucial predictor for the long-term outcome [7,8], but has also been reported to be a major argument against OPCAB [11,24,25]. Our findings are supported by Puskas et al [8] who demonstrated feasibility of complete revascularization using OPCAB.…”
Section: Discussionsupporting
confidence: 82%
“…Off-pump coronary artery bypass surgery (OPCAB) has a comparable risk-adjusted mortality and morbidity as on-pump CABG [6][7][8]. Current reports suggest OPCAB to be superior for high-risk patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The most recent trial demonstrated decreased blood-product requirement, myocardial enzyme release, and length of hospitalization in beating-heart surgery patients. 18 Of the 3 published trials, 2 are single-surgeon experiences, and as such, the potential for bias in end points that are discretionary treatments (decision to extubate, discharge, and transfuse) is an important consideration. Moreover, the majority of these trials excluded high-risk patients, which brings into question the generalizability of the results.…”
Section: See P 810mentioning
confidence: 99%
“…Additionally, the duration of the ICU stay for patients submitted to the surgery without ECC was significantly shorter than for patients that underwent the surgery with ECC, similarly to that observed by another study 11 . Other results, concerning the cost analysis, did not show a decrease in the ICU stay for patients without ECC; however, all of them showed a shorter intubation time [16][17][18] .…”
Section: Discussionmentioning
confidence: 95%
“…Several studies did not use stabilizers in all patients and, in many of them the equipment is re-usable [8][9][10][11][12][13][14][15][16][17][18] . The criteria for these procedures have not been discussed in depth; however, to ensure our patients' safety, especially those in whom the procedure involved the revascularization of latero-posterior wall of the left ventricle, the use of stabilizer was considered mandatory for all the patients in this group.…”
Section: Discussionmentioning
confidence: 99%